Investigate the Influence and Moderators of the Embarrassment on the Continual Usage and Knowledge Sharing Intention in Virtual Communities - Sheng-Cheng Lin (International Journal of Informatics and Information Systems, 2021)
Embarrassment has been an important research issue in the domain of management. Previous studies indicated when embarrassment occurred between sales and customers, it could reduce the customers' intention to visit the store again. Virtual communities are also places for interaction between members; therefore, embarrassment could occurred as well. Goffman’s dramaturgic theory can be perfectly applied to the settings of virtual communities. They both address the interaction facet between people. Dramaturgic theory can also elaborate the occurrence of embarrassment. Thus, this study aims to resolve the possible reasons inducing embarrassment by dramaturgic perspective, and investigate the influence and moderators of embarrassment on members' continual usage and knowledge sharing intention towards virtual communities. In addition, two sets of interference variables were derived based on virtual community characteristics, and their influence on the above-mentioned correlations was analyzed. The research results can be a good reference for virtual community operators and managers to help them understand those causes of embarrassment that have a negative impact on those community members’ intentions, and to reflect on how they can reduce those causal factors by tweaking the design of community platforms.